Comparison of the internet usage levels amongst final year students of faculty of medicine and health colleges in Turkey: According to the gender variable - Gürol, Aysun (My University, 2010)
The use of internet is becoming widespread all over the world including the health sector. Internet has been increasing its importance for individuals in the health sector for purposes of increasing speed and efficiency of surgeries, sharing patients' data, storing information in the database. The aim of this study is to examine the relationship between a group of medicine faculty and health college students' level of internet use and their views about the internet with regard to their gender. The final year students of the faculty of medicine and health college at Firat University constituted the sample of the research. Of 219 final year students, 155 students who were present when the research was conducted constituted the sample of this study. A Likert type questionnaire was used to determine students' level of internet use. The questionnaire was developed previously by the researcher and the test of its reliability and validity was performed. The study reveals that 14.8% of the students use internet for 2 h or more in a week and 72.9% of students do not use internet in weekdays at all. The findings also showed that 76.1% of the students know the concept of 'internet' for more than four years, and 61.9% of the students access to internet from the internet cafes, 48.4% of the students use internet for academic purposes and 63.9% of the students want to set up their web pages on the internet. In the light of research findings, it is thought that internet-based and interactive lesson applications are inevitable education tools for education faculties of medicine and health colleges in the future. According to the findings, female students seem to log into internet less but stay connected more, and students mostly prefer to use internet cafes for internet access. In these cafes, internet is used mainly for academic purposes. It is expected that this study will provide some educational implications that enable effective use of internet in health education and a cooperative learning environment that would allow male and female students to study collaboratively. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Distance learning; Health education; Hybrid education; Internet